Metals process simulation - Furrer, D. U.; Semiatin, S. L. (ASM International, 2010)
This Handbook provides insight into the integration of modeling for simulation of manufacturing processing. The metals industry is moving toward an integrated computational materials engineering approach (ICME). This provides engineers with accurate predictions of material and process behavior to avoid or reduce costly trial-by-error and prototyping methods of development. The table of contents illustrates the depth and breadth of the processes addressed. This area of engineering has been advancing rapidly, accruing the benefits of reduced manufacturing costs and improved component design. This book serves as a reference to these developments.
Keywords: Metals -- Handbooks, manuals, etc.; Metallurgy -- Simulation methods.; Metal-work -- Simulation methods.; elektronické knihy; electronic books